Investigating the relationship between Survivin and Tank-Binding Kinase 1 in cancer cells - Daly, Lauren (2021)
Survivin is a multi-functional, homeostatic regularity protein with opposing roles in cell proliferation and cell death. Survivin overexpression is a key biomarker for the identification of oncogenic cells. Within cancer, survivin is contributes to the inhibition of cell death and dysregulation of proliferation. Within the cell, survivin is either located with the DNA during mitosis or within the cytoplasm. However, a unique oncogenic pool of survivin has been found within the mitochondria. Evidence has shown that the mitochondrial pool of survivin is linked to the inhibition of apoptosis. However, it is still unknown how this pool of survivin develops.